Determinación de las limitaciones tributarias que se presentan en el Estado Colombiano frente al TLC con Estados Unidos y sus efectos. (2022)
On the tenth anniversary of the take effect of the Free Trade Agreement between the Republic of Colombia and the United States of America, this document seeks to resolve the question: What are the tax limitations that are provided in the Colombian state against the FTA with the United States? For this, a table explains each Category of Tariff Relief, the productive sectors involved and if the agreed period for these products to be free of tariffs has already expired. From where it will be developed that the vast majority of the products on the Schedules of Colombia and the United States are in the relief categories A, B, C and F, which are already free of tariffs. Next, the data from the DANE Export and Import technical bulletins are used, which allows determining the products exported and imported by Colombia to the world and specifically from the US, where the value per sector is specified in dollars (USD) FOB, in where it was concluded that one year after the entry into force of the trade agreement, Colombia's exports to the United States decreased. In 2014, imports from the United States decreased and, additionally, a negative trade balance began to occur. Number three sets out some of the effects that have occurred with the entry into force of the Free Trade Agreement, such as external collection, which has not been affected by the signing of Free Trade Agreements with other countries. and the increase in income from External IVA. In competitiveness, where it is concluded that the most affected has been the Colombian field in products such as corn, soybeans and barley, whose national production cannot compete with the United States. Finally, in employment, which in the agricultural sector has two faces, unemployment for people with non-competitive products, and 200,000 direct jobs in flower exports.